Upaya Pencegahan Penyakit Ayam Kampung Untuk Meningkatkan Produksi di Kelompok PKH Desa Podosoko Candimulyo Magelang - Rasminati, Nur; Utomo, Setyo; Sudrajat, Ajat (Farmers : Journal of Community Services, 2026)
The purpose of community service is to increase the income of PKH members of Podosoko Village, Candimulyo, Magelang through the prevention of free-range chicken diseases. The activity starts from May to November 2025. The implementation method is through the technique of raising awareness of the mindset of traditional livestock to business-oriented breeding, disease prevention in free-range chickens, intensive cage making training (demonstration plot), making local microbial starters (MOL) from rice, selection of good chicken seeds, understanding of traditional medicines, assistance in chicken brood and disease prevention with regular vaccination and assistance. This activity is in collaboration with the Magelang Regency Government. The results of the activities achieved were that 60% of participants actively participated in the FGD, 85% understood the importance of doing free-range chicken business, 70% of participants considered the activities to be in accordance with their needs. Chickens fed MOL lay eggs (40%), participants were able to make MOL and were ready to practice it 25%, active in maintenance in the demonstration plot there were 4 people (40%). Participants were very enthusiastic (practicing) the production triangle by 60% by realizing the need to prevent chicken disease (75%) and feeding locally made with fermentation technology (80%) and felt able to be a native chicken entrepreneur with a business orientation through an intensive cage system (85%). It was concluded that this activity was very beneficial for the PKH group, improving knowledge and skills in raising free-range chickens. To ensure the sustainability of this activity, it is coordinated with the Magelang Regency Livestock and Fisheries Office